HUBUNGAN KREATIVITAS DAN HASIL BELAJAR DALAM MODEL PROJECT-BASED LEARNING: SEBUAH STUDI LITERATUR BERBASIS ANALISIS KORELASI - Devina Santri; Andrini Rosa Putri Siregar; Almira Amir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
21st-century learning emphasizes the importance of mastering higher-order thinking skills, including creativity, as a key ability to solve problems and generate new ideas. Project-Based Learning (PjBL) is regarded as an effective instructional model for fostering creativity through authentic, collaborative, and product-oriented project activities. This literature review aims to examine the relationship between students’ creativity and learning outcomes in the implementation of PjBL by reviewing quantitative studies that employ correlation analysis. The reviewed articles were sourced from national journals and proceedings published between 2021 and 2025 that include variables of creativity and learning outcomes and are relevant to PjBL. The analysis was conducted by examining the types of correlation, sample sizes, and correlation coefficient values. The findings indicate a positive and significant relationship between creativity and learning outcomes, with correlation strengths ranging from moderate to very strong. These results confirm that creativity plays an important role in the success of project-based learning and should be developed in a systematic manner.